A SNP, Gene, and Polygenic Risk Score Approach of Oxytocin‐Vasopressin Genes in Adolescents' Loneliness. (29th January 2019) - Verhagen, Maaike; Verweij, Karin J. H.; Lodder, Gerine M. A.; Goossens, Luc; Verschueren, Karine; Van Leeuwen, Karla; Van den Noortgate, Wim; Claes, Stephan; Bijttebier, Patricia; Van Assche, Evelien; Vink, Jaqueline M.
Abstract : Not much is known regarding underlying biological pathways to adolescents' loneliness. Insight in underlying molecular mechanisms could inform intervention efforts aimed at reducing loneliness. Using latent growth curve modeling, baseline levels and development of loneliness were studied in two longitudinal adolescent samples. Genes ( OXTR, OXT, AVPR1A, AVPR1B ) were examined using SNP‐based, gene‐based, and polygenic risk score (PRS) approaches. In both samples, SNP‐ and gene‐based tests showed involvement of the OXTR gene in development of loneliness, though, significance levels did not survive correction for multiple testing. The PRS approach provided no evidence for relations with loneliness. We recommend alternative phenotyping methods, including environmental factors, to consider epigenetic studies, and to examine possible endophenotypes in relation to adolescents' loneliness.